Tuberkulosis laten pada anak - Flora Mindo Panjaitan; Ridwan M. Daulay; Wisman Dalimunthe; Rini Savitri Daulay (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Nowadays, TB continues to be a major health problem and a global public health issue. Latent tuberculosis is the clinical state characterized by the presence of lasting mycobacteria specific T-cell responses, assessed by tuberculin skin test (TST), in case of the absence of clinical and radiological manifestation of tuberculosis. Detection and treatment of latent tuberculosis is a key strategy in the control of TB. The Quantiferon TB Gold and T-Spot TB did not show higher sensitivity neither specificity than TST in detection latent TB in children. Tuberculin skin test is remain a recommended method to diagnose latent TB in children. Keywords : latent tuberculosis; children